European EADV network on assessment of severity and burden of Pruritus (PruNet): first meeting on outcome tools - Ständer, Sonja; Weisshaar, Elke (Journal of the European Academy of Dermatology and Venereology, 2016)
Background Chronic pruritus is a frequently occurring symptom of various dermatoses that causes a high burden and impaired quality of life. An effective anti pruritic therapy is important for the patient, but its effectiveness is difficult to evaluate. Diverse methods and interpretations of pruritic metrics are utilized in clinical trials and the daily clinical practice in different countries, resulting in difficulties comparing collected data. Methods We founded a European Network on Assessment of Severity and Burden of Pruritus (PruNet) that is supported by the EADV. PruNet consists of 28 experts from 15 EU countries (21 dermatologists, 5 medical informaticists, 2 psychologists) and aims to unify the assessment of itch in routine dermatological care. Following a preliminary survey, a consensus conference was held in order to agree upon the prioritization of patient-reported outcome tools. Results Through utilizing the Delphi method, it was agreed that tools for measuring itch intensity (ex. the visual analogue scale) and quality of life (ex. ItchyQoL) are of primary importance and should urgently be foremost validated. Conclusion The validation and harmonization of standards are needed for the improvement of quality care for patients suffering from pruritic dermatoses. This summer, the first validation studies in several EADV member countries already began.
First published: 15 September 2015
Gesehen am 13.05.2020